Highly Flexible, High-Performance, and Stretchable Piezoelectric Sensor Based on a Hierarchical Droplet-Shaped Ceramics with Enhanced Damage Tolerance - Xu, Qianqian (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Authors. Advanced Materials published by Wiley‐VCH GmbH.